ANTIOXIDANT ACTIVITY TEST OF THE ETHANOL EXTRACT OF AVOCADO SEED (Persea americana Mill.) USING THE FRAP METHOD - Ohorela, Indah Kartika; Maryam, St.; Suhaenah, Asriani (Makassar Pharmaceutical Science Journal (MPSJ), 2024)
Avocado seeds (Persea americana Mill.) are a plant that is useful as a traditional medicine. The ethanol extract of avocado seeds contains several secondary metabolite compounds, namely alkaloids, triterpenoids, tannins, flavonoids and saponins. The aim of this research was to determine the antioxidant activity contained in avocado seed extract (Persea americana Mill.). using the FRAP method which was measured with a UV-Vis spectrophotometer at a wavelength of 794 nm. Extraction of avocado seeds (Persea americana Mill.) using the maceration method using 96% ethanol solvent. The results show that the antioxidant activity of the ethanol extract of Avocado Seeds is 42.448 mgQE/g of extract, which means that every 1 gram of ethanol extract of avocado seeds (Persea americana Mill.) is equivalent to 42,488 mg of quercetin.